Co-Teaching an Online Action Research Class / Co-enseignement et classe de recherche-action en ligne - Brent G Wilson; Jennifer Linder VanBerschot (Canadian Journal of Learning and Technology, 2014)
Two instructors report our experience co-teaching an action research (AR) required as part of an e-learning master’s degree. Adopting a practice-centered stance we focus on the course activities of participants (instructors and students), with particular attention to the careful crafting of course elements with the goal of achieving an excellent learning experience for students. The case narrative describes the course and ways in which we have modified the course based on a variety of considerations. We also outline problems and areas still in need of improvement. We reflect on the role of theory in our own pursuit of excellence, and the role of theory in our students’ inquiry processes. We find that theory is just another tool or resource to apply to the work, with the core concerns being the needs of students and the learning environment.